L.A. Detective - Prowse, Philip (n.p. : Heinemann)
Los Angeles. Len Samuel is a privae detective. Carmen Blanche is a prisoner of The Young Ones. They want 100000 dollars. Carmen's father is a rich man but he also is a bad man. Len samuel has a dangerous job.
Keywords: Fiction -- Easy